Population dynamic of Anomalocardia brasiliana (Mollusca, Bivalvia, Veneridae) in the estuary of River Paciência in Raposa, Maranhão state - Santos, Juan Jethro Silva; Martins Terceiro, Abraão; Yauri, Walter Luis Muedas (Anuário do Instituto de Geociências, 2014)
Mollusk occurrence in Maranhão coast is significant, serving as sources of income and livelihood for many communities. An example of mollusk species related to this potential is the Anomalocardia brasiliana (Gmelin, 1791), which has great importance for the population of Raposa - Maranhão State, on Maranhão Island. Monthly, samples were collected during August to December 2010 and March to June 2011, that carried out important information such as biometric data, condition factor and density. These variables showed that the bodies-size throughout the sampling period, except that of August, are suitable for human consume, averaging over 20mm. Therefore, it was also observed a decreased of the condiction factor in the months of August and December, probably related to stress, such as the spawing period of the species or anthropogenic pressure in the region, as there is a large extraction in the site, through an unsustainable way. The density of organisms was high in terms of biomass, which showed that an average of 3.16 tons in an area of 6,007.5 mÂ², which compared with extensive cattle farms, depending on management, it becomes more productive, economically, ecologically and financially.